Network analysis uncovers the master role of WRKY transcription factors in Arabidopsis thaliana response to N-acyl homoserine lactones - Yongming Duan; Min Han; Maja Grimm; Adam Schikora (CABI Agriculture and Bioscience)
Abstract Background Plants can perceive bacterial molecules such as the quorum sensing signals N-acyl homoserine lactones (AHL), thus modifying their fitness in response to environmental factors. Even though the benefits conferred by AHL depend on various hormone signaling pathways, the understanding of AHL signaling, especially the response to AHL presence, remains largely unknown. Methods Weighted gene co-expression network analysis (WGCNA), multi-omics network analysis, and reverse transcription quantitative PCR (RT-qPCR) assays were used to identify key genes in AHL signaling. Results To obtain comprehensive insights on AHL signaling, we integrated available transcriptome data from Arabidopsis thaliana exposed to different single or multiple AHL molecules and performed a weighted gene co-expression network analysis. We identified several key genes regulated in plants exposed to multiple AHL molecules. Multi-omics network analysis and RT-qPCR assay revealed a potential role of WRKY transcription factors. Conclusions Results presented here offer good indications for exploring the mechanism of plants' response to bacterial signaling molecules, which could further support the application of AHL-producing bacteria in sustainable agriculture.